1968
DOI: 10.1071/bi9681277
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of Heliotrine by A Rumen Microorganism

Abstract: SummaryA small Gram-negative coccus, which brings about the reductive fission of the hepatotoxic pyrrolizidine alkaloids, has been isolated from the rumen contents of Australian Merino sheep. The organism was cultured in a partially defined medium, without rumen fluid, but containing yeast extract. Strictly anaerobic conditions and the presence of carbon dioxide were essential for growth. With limiting quantities of yeast extract, growth was greatly stimulated by any of several carbohydrates or moderately stim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

1970
1970
1997
1997

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(12 citation statements)
references
References 18 publications
2
10
0
Order By: Relevance
“…Some studies have shown that the inhibition of methanogenesis with chloral hydrate or halogenated methanes actually enhanced heliotropine metabolism (24). These results suggest that PA-metabolizing organisms may compete with methanogens for reducing equivalents and that excess electron donors may augment the reductive fractions involved in PA dissimilation (23,24,31). The lack of PA activity in the denitrifying consortium may be due to the fact that either (i) denitrifying bacteria do not metabolize PA or (ii) the presence of nitrate inhibited the methanogenic consortium such that it could not metabolize the amended PA.…”
Section: Discussionmentioning
confidence: 97%
“…Some studies have shown that the inhibition of methanogenesis with chloral hydrate or halogenated methanes actually enhanced heliotropine metabolism (24). These results suggest that PA-metabolizing organisms may compete with methanogens for reducing equivalents and that excess electron donors may augment the reductive fractions involved in PA dissimilation (23,24,31). The lack of PA activity in the denitrifying consortium may be due to the fact that either (i) denitrifying bacteria do not metabolize PA or (ii) the presence of nitrate inhibited the methanogenic consortium such that it could not metabolize the amended PA.…”
Section: Discussionmentioning
confidence: 97%
“…Two of the potentially toxic alkaloids, heliotrine and lasiocarpine, are reduced to non-toxic I-methylene and 7-hydroxy-lmethyl derivatives in the rumen (Lanigan and Smith, 1970;Russell and Smith, 1968;Dick et al, 1963). These compounds and their metabolites have many pathological effects on the liver, kidney and respiratory systems.…”
Section: Alkaloidsmentioning
confidence: 99%
“…Finally, these data together with the results of Russell and Smith (1968), who showed that the micrococcus caused a reductive fission of the pyrrolizidine alkaloids, tend to suggest that this bacterium may be non-specific in its hydrogenating capacity.…”
Section: Di8cus8ionmentioning
confidence: 99%
“…Cultures of the rumen miorooooous were isolated from rumen oontents by prooedures outlined previously (Russell and Smith 1968). The organism was inoubated for 24 hr at 38°C under anaerobio oonditions, in oarbon dioxide, in a medium desoribed by Russell and Smith (1968) oontaining [14C]fatty aoid (5 p.Ci, 0·1 p.mole) oomplexed to bovine serum albumin (Kessler, Demeny, and Sobotka 1967, method B).…”
Section: Experimental (A) I80lation and Incubation Of The Micrococcusmentioning
confidence: 99%
See 1 more Smart Citation